Assessing energy return on investment for harvest of wild Nodularia spumigena during blooms in the Baltic Sea. (13th July 2021) - Pechsiri, Joseph S.; Gröndahl, Fredrik
Abstract: Recurring summer cyanobacteria blooms in the Baltic Sea has gained academic interests for decades. The harvest of wild cyanobacteria, for example, Nodularia spumigena, during summer blooms in the Baltic Sea has been studied in the past but lacked evaluation for environmental and economic performances. This study provides a first‐hand assessment of environmental and economic performance from an energy perspective, using energy return on investment (EROI) as evaluation method where harvest of biomass and the downstream conversion of biomass to biogas and biofertilizer are considered for Gotland, Sweden. Energy analysis results indicate fuel consumption during harvest and transport operations to be the major energy consumer. Traditional sailing boats have been suggested as an alternative. Overall, when considering only biogas yield and usage of sailing boats, a break‐even EROI of 1 is achieved. When including biofertilizer as product, a breakeven EROI of 1 is also achieved. Depending upon the biomass concentration in the Baltic Sea at the time of harvest, an EROI > 6 is possible, surpassing the economic viability EROI benchmark of 3, indicating the importance of nutrient recovery as the driver for harvest of wild cyanobacteria biomass during blooms in the Baltic Sea. This article met the requirements for a gold‐gold JIE data openness badge described at http://jie.click/badges .